Damage sequence in thin-ply composite laminates under out-of-plane loading. (August 2016) - Wagih, A.; Maimí, P.; González, E.V.; Blanco, N.; de Aja, J.R. Sainz; de la Escalera, F.M.; Olsson, R.; Alvarez, E.
Abstract: The study of the damage sequence in polymer-based composite laminates during an impact event is a difficult issue. The problem can be more complex when the plies are thin. In this paper, quasi-static indentation tests were conducted on thin-ply laminates to understand qualitatively the damage mechanisms and their sequence during low-velocity impact loading. TeXtreme® plain weave plies were used with two different thicknesses, 0.08 mm and 0.16 mm (referenced as ultra-thin-ply and thin-ply, respectively), and tested under different load levels. Load–displacement curves were analyzed and the extent of damage was inspected using optical microscopy and ultrasonic technique. The results showed that the damage onset occurs earlier in thin-ply laminates. The damage onset in thin-ply laminates is matrix cracking which induces delaminations, whereas for ultra-thin-ply laminates is due to delaminations which are induced by shear forces and small amount of matrix cracking. Moreover, the fiber breakage appears earlier in ultra-thin-ply laminates.